HUBUNGAN PEMBELAJARAN DARING DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR SISWA DALAM PELAJARAN PAI MTs KECAMATAN TIRTAMULYA KARAWANG 2021 - Rijal Ansori; Yayat Suharyat; Asep Dudin Abdul Latip (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
The problems encountered in the field are online learning requires a fee, limited families have cell phones, unstable internet network signal, low parental attention to PAI learning achievement. The purpose of this study was to determine the relationship between online learning and student achievement with parental attention to PAI lessons in Tirtamulya District, Karawang. The research method uses Quantitative (Statistics). The result of the research is that there is a significant relationship between online learning and student achievement. This is evidenced by the value of sig = 0.206 > 0.05. Thus, H0 is rejected and it can be concluded that there is a significant correlation/relationship between online learning (X1) and student achievement (Y) in PAI lessons. There is a significant relationship between parental attention and student achievement. This is evidenced by the value of sig = 0.188 > 0.05. Because the significance value = 0.188 > 0.05 then with Thus H0 is rejected and it can be concluded that there is a significant positive correlation/relationship between parental attention (X2) and student learning achievement (Y) in PAI lessons. There is no significant joint interaction relationship between online learning and parental attention to learning achievement students. This is evidenced by the magnitude of the calculated F value = 3.133, and sig = 0.052 > 0.05. Thus, H0 is accepted and it can be concluded that together there is no significant correlation (relationship) between online learning (X1) and parental attention (X2) on student achievement (Y) in PAI lessons.